The rsmA mutant from Pseudomonas aeruginosa ID4365 is a non-virulent strain that is suitable for pyocyanin and phenazine-1-carboxylic acid production - Misael Josafat Fabian Del-Olmo; Luis Fernando Montelongo-Martínez; Gisela Viridiana Villafañe-Barajas; Abigail González-Valdez; Veronica Roxana Flores-Vega; Roberto Rosales-Reyes; Marco Elias Gudiño-Zayas; Thelma Rizo-Pica; Raunel Tinoco-Valencia; Adelfo Escalante; Gloria Soberón-Chávez; Miguel Cocotl-Yañez (PLoS ONE, 2025)
Phenazines are compounds of medical and biotechnological interest due to their antimicrobial and antitumoral properties. Pseudomonas aeruginosa , a Gram-negative bacterium, naturally produces phenazines such as pyocyanin and phenazine-1-carboxylic acid (PCA). These phenazines can generate reactive oxygen species, which increase oxidative stress in susceptible cells and ultimately lead to their death. Pyocyanin can inhibit the growth of human bacterial pathogens, while PCA serves as a potent antifungal agent that can prevent and control crop diseases. The environmental strain P. aeruginosa ID4365 overproduces pyocyanin, and its derivative strain IDrsmA, which carries a mutation in the rsmA gene, presents a fivefold increase in pyocyanin production compared to the wild-type strain. This mutant is therefore a promising candidate strain for enhancing phenazine production. In this work, we found that the IDrsmA strain has an inactive type three secretion system and is non-cytotoxic. Unlike the wild-type strain ID4365, the IDrsmA strain was unable to infect and kill Galleria mellonella larvae or mice. Besides pyocyanin, the IDrsmA strain also produced increased levels of PCA and 1-hydroxyphenazine. In addition, we showed that the deficient phosphate medium, PPGAS, is the best phenazine production medium compared to PPM or King A media. By optimizing culture conditions, we increased pyocyanin production up to 298 μg/mL using strain IDrsmA. We further modified the IDrsmA strain to produce only PCA, achieving a production level of 303 μg/mL, which is 10 times higher than that of the wild-type strain. Thus, the IDrsmA strain is non-virulent and suitable for phenazine production.